Case report: Pacemaker lost capture after acute myocardial infarction in a patient with left circumflex coronary artery occlusion - Wu, Zhihong; Tang, Jianjun; Zhu, Qingyi; Hu, Lin; Liu, Zhenjiang; Li, Xuping; Liu, Qiming; Zhou, Shenghua; Chen, Mingxian (Frontiers in Cardiovascular Medicine, 2022)
A 71-year-old female with a dual-chamber pacemaker was presented to our hospital because of chest pain. She was diagnosed with unstable angina. On day 7, the patient suddenly occurred cardiopulmonary arrest due to inferior ST segment elevation myocardial infarction (STEMI). Pacemaker lost capture was suspected and confirmed by a pacemaker check with high pacing threshold and low sensing parameter. Emergency coronary angiography revealed a large filling defect remained due to extensive thrombus in the proximal left circumflex (LCX) with TIMI grade 2 flow, and then repeated thrombus aspiration was performed. After reperfusion, the parameters of right ventricular lead were gradually returned. We conclude that the loss of the right ventricular lead pacing occurred in this case of ACS inducing by LCX thrombus due to a LCX supplying the right ventricular septal.